Designing Thesaurus with Multilevel Hierarchy Systems (LIS TODAY, 2025)
Information retrieval systems are designed to retrieve information from a database  quickly and accurately. A multilevel hierarchy is a recursive process that consists of  logically related levels with relation and is represented in a linear sequence. They are  intricate among the parts of a whole, statistically or dynamically. This paper explores  the significance of incorporating multilevel hierarchy systems in designing a thesaurus.  It aims to enhance the efficiency and usability of the linguistic resources. Thesauri are  crucial in information retrieval, establishing semantic relationships between words.  Traditional thesauri have employed a single-level hierarchy, but recent advancements  in information organization and retrieval call for more sophisticated structures to  accommodate the complexities of language and user needs. This article presents the  methodologies and benefits of designing thesauri with multilevel hierarchy systems,  which not only enhance the efficiency and usability of linguistic resources but also  significantly improve the accuracy and speed of information retrieval.
Keywords: Multilevel Hierarchy; MultiTes; Semantic Web; Thesaurus; User Experience